2012
DOI: 10.1590/s1806-37132012000500011
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados às complicações em crianças pré-escolares com pneumonia adquirida na comunidade

Abstract: Objective: To identify socioeconomic factors and clinical factors associated with the development of complications in preschool children hospitalized with community-acquired pneumonia (CAP). Methods: This was a prospective longitudinal study involving children (12-59 months of age) diagnosed with CAP and admitted to the pediatric wards of two hospitals in the metropolitan area of Campinas, Brazil. Children with cystic fibrosis, heart disease, pulmonary malformations, neurological disorders, or genetic diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
3
15
0
4
Order By: Relevance
“…( 4 ) Interestingly, the length of hospital stay found in the present study was quite similar to that reported in a study involving 33 Brazilian children with empyema (i.e., 12 days). ( 6 ) In addition, serotype 1 was one of four serotypes found in both PE and BPP (i.e., 14, 1, 6B, and 5), a finding that is consistent with those of the study by François et al., ( 4 ) which was conducted in a developed country.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…( 4 ) Interestingly, the length of hospital stay found in the present study was quite similar to that reported in a study involving 33 Brazilian children with empyema (i.e., 12 days). ( 6 ) In addition, serotype 1 was one of four serotypes found in both PE and BPP (i.e., 14, 1, 6B, and 5), a finding that is consistent with those of the study by François et al., ( 4 ) which was conducted in a developed country.…”
supporting
confidence: 89%
“…( 4 ) Curiosamente, o tempo de hospitalização no presente estudo foi bastante semelhante ao relatado em um estudo com 33 crianças brasileiras com empiema (isto é, 12 dias). ( 6 ) Além disso, o sorotipo 1 foi um dos quatro sorotipos encontrados tanto nas crianças com EP como naquelas com PPB (isto é, os sorotipos 14, 1, 6B e 5), um achado que está de acordo com os do estudo de François et al, ( 4 ) realizado em um país desenvolvido.…”
unclassified
“…Despite the advances of mankind in recent years, high rates of infant mortality are still verified mainly in developing countries. Among the five main causes are the acute respiratory infections, responsible for the death of about three million children under five years per year [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acute respiratory infection is one of the 5 main causes of death in children under 5 years of age in developing countries. 1 About 40% of children needing medical attention suffer from acute respiratory infection 2 , where community-acquired pneumonia is the most severe, causing 80% of deaths 3,4 . In Brazil, acute lung diseases are responsible for 11% of deaths in children under 1 year old and 13% in the age group between 1 and 4 years 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the various risk factors associated with pneumonia are: low socioeconomic status, malnutrition, low birth weight, lack of breastfeeding, family crowding, environmental pollution, climate variation and passive exposure to cigarette smoke 3,6,8,9,16,17 .…”
Section: Introductionmentioning
confidence: 99%